Cellulose acetate layer effect toward aluminium corrosion rate in hydrochloric acid media - Andarany, K.S. (Institute of Physics Publishing, 2017)
Corrosion occurs due to the oxidation and reduction reactions between the material and its environment. The oxidation reaction defined as reactions that produce electrons and reduction is between two elements that bind the electrons. Corrosion cannot be inevitable in life both within the industry and household. Corrosion cannot eliminate but can be control. According to the voltaic table, Aluminum is a metal that easily corroded. This study attempts to characterize the type of corrosion by using a strong acid media (HCl). Experiment using a strong acid (HCl), at a low concentration that occurs is pitting corrosion, whereas at high concentrations that occurs is corrosion erosion. One of prevention method is by using a coating method. An efforts are made to slow the rate of corrosion is by coating the metal with "cellulose acetate" (CA). cellulose acetate consisted of cellulose powder dissolved in 99 acetic acid, and then applied to the aluminum metal. Soaking experiments using hydrochloric acid, cellulose acetate is able to slow down the corrosion rate of 47 479. © Published under licence by IOP Publishing Ltd.